PENERAPAN PENDEKATAN KONSTRUKTIVISTIK DALAM PENDIDIKAN BAGI ANAK USIA DINI DALAM RANGKA PENINGKATAN KUALITAS PEMBELAJARAN - Nofri Dodi (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2016)
Abstract Education is a conscious effort made by adults to change behavior for the better and meaningful way. Changes in behavior should be taken seriously by the continuous efforts through meaningful learning. Meaningful learning will be able to make changes on the cognitive, affective and psychomotor aspect. The three domains of educational objectives will be able to be reached, with active learning model that is being done to construct their own knowledge through learning activities designed. Constructivist learning is learning which is able to change the old style of teaching a of a teacher who has always played an active role into a style of teaching where the teacher acts as a facilitator to enable students to learn on their own, learn to interact in a group, being able to responsible for achieving the results of individual learning, by providing guidance and facilitate student learning. Keywords: Quality of Learning, Constructivistic Approach, Early Childhood